Stable isotope analysis on human remains from the final Early Holocene in the southern Puna of Argentina: The case of Peñas de las Trampas 1.1 - Killian Galván, Violeta Anahí (2015)
In this work are presented the results of isotopic analyses made on bone remains of human individuals (n = 6) from the southern Puna of Argentina dated to the final Early Holocene (ca. 8230–8000 BP). They were found in structures located in Peñas de las Trampas 1.1, a rockshelter at 3582 m.a.s.l. in Antofagasta de la Sierra, in the southern Argentinian Puna. They contain multiple secondary burials. Bone fragments were recovered from at least six individuals, three in each structure. Stable isotopes of Carbon (δ13C) and Nitrogen (δ15N) analysis were aimed at defining aspects related to the palaeodiet of the six individuals within the palaeo-economic subsistence spectrum typical of hunter–gatherers. It is worth noting that these human remains are among the earliest from North-Western Argentina, where funeral practices are related with the transportation of certain anatomical parts. The palaeodietary inference considers, on the one hand, the extreme aridity of this geographical area and its impact on the isotopic ecology. And, on the other, it takes into account the fact that four of the six individuals under study were breastfed infants. The results are in agreement with the expected values of the period, which has been characterized as the beginning of the arid Altithermal.